Flavanoids fromthe Stembark of Chisocheton pentandrus(Meliaceae) - Supriatno Supriatno; Ace Tatang Hidayat; Kindi Farabi; Fajar Fauzi Abdullah; Nurlelasari Nurlelasari; Tati Herlina; Unang Supratman; Khadijah Awang (Syarif Hidayatullah State Islamic University, 2017)
Two flavanoid compounds, catechin (1) and epicatechin (2), have been isolated from the stembark of Chisocheton pentandrus. The chemical structure of compounds1and2were identified byspectroscopic data including, UV, IR, NMR (1H, 13C, DEPT 135°, HMQC, HMBC, 1H-1H COSY) and MS and by comparing with previously reported spectral data. Compounds 1 and 2, were isolated in this plant for first time and showed no cytotoxic activity against MCF-7 breast cancer cells.